Barriers to and facilitators of adherence to intravenous chemotherapy among breast cancer patients at a tertiary hospital in the Western Cape - Kepkey, Brigitta Blumé (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.